DEVELOPMENT OF AN INTELLIGENT EGG INCUBATOR SYSTEM BASED ON ARDUINO - Alisher Khamroev, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Artificial incubation systems play a crucial role in modern poultry farming by ensuring stable environmental conditions for embryo development. This study presents the design and implementation of an intelligent egg incubator based on the  Arduino  microcontroller  platform  integrated  with  environmental  sensors  and automated  control  mechanisms.  The  proposed  system  monitors  temperature  and humidity  in  real  time  and  automatically  regulates  heating,  ventilation,  humidity generation, and egg turning processes. A real-time clock module ensures scheduled egg rotation,  while  IoT  integration  enables  remote  monitoring.  Experimental  results demonstrate improved environmental stability and increased hatchability compared to manual  incubation  methods.  The  developed  system  provides  a  low-cost,  energy-efficient, and scalable solution.